Composition comprising carbon nanotubes and at least one polymer with low or non solvent

By developing carbon nanotube/polymer powder compositions, the problems of large amount of solvent and poor electrical performance required for carbon nanotube dispersion in battery electrodes are solved, and the preparation of high-performance electrodes and the reduction of carbon footprints are achieved, providing no Possibility of solvent electrode preparation.

CN119156345APending Publication Date: 2024-12-17ARKEMA FRANCE SA
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202380038541.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-05-06
Filing Date
2023-05-04
Publication Date
2024-12-17

AI Technical Summary

Technical Problem

The use of existing carbon nanotubes in battery electrodes requires a large amount of solvent for dispersion, resulting in a large carbon footprint and poor electrical performance, and the existing dry routes cannot prepare high-performance electrodes under optimal conditions.

Method used

A composition in powder form in a carbon nanotube/polymer mass ratio of less than 100/5 has an apparent specific surface area of ​​0.11 to 0.5 g/cm3 and 50 to 350 m2/g through fog Preparation of the sculpting or extrusion process enables redispersion during electrode preparation, reducing solvent use and improving electrical properties.

Benefits of technology

A high performance quality during electrode preparation, a carbon nanotube-polymer composition comparable to the liquid route is achieved, reducing material transport volume and improving conductivity, providing the possibility of solvent-free electrode formulation.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005118973910000111
    Figure BDA0005118973910000111
  • Figure BDA0005118973910000121
    Figure BDA0005118973910000121
  • Figure BDA0005118973910000131
    Figure BDA0005118973910000131
Patent Text Reader

Abstract

The present invention relates to a carbon nanotube composition which can be applied in solid form, i.e. In the absence of a solvent. These compositions comprise at least one polymer and are readily dispersible in formulations for the production of electrodes of batteries, and in particular Li-ion batteries, in liquid or solid processes. The invention also relates to a process for obtaining these powders, to the use thereof in the manufacture of electrodes for batteries and to batteries comprising them.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to compositions comprising carbon nanotubes in powder form. These compositions in powder form comprise at least one polymer and are easily dispersed in solvent-containing or solvent-free formulations for the manufacture of electrodes for batteries, in particular Li-ion batteries. Background Art

[0002] Carbon nanotubes are made from rolled-up sheets of graphite. Nanotubes can consist of a single sheet and are then called single-walled nanotubes (SWNTs). Nanotubes can also consist of multiple concentric sheets and are then called multi-walled nanotubes (MWNTs). Carbon nanotubes are therefore ideal candidates for a wide range of applications, particularly as additives for improving resistance in materials and devices (devices) such as battery electrodes (including anodes and cathodes), especially lithium-ion batteries. These improvements in battery performance form part of the development of electric vehicles and are therefore part of the fight against global warming.

[0003] For example, carbon nanotubes obtainable in known synthesis processes cannot be formulated directly with the components used in the composition of battery electrodes, because they appear in the form of tangled bundles or balls. Their relative density is too low, typically less than 0.1, and the obtained formulations do not exhibit the improvement in conductivity that could be expected due to their presence.

[0004] Today, their use requires a pre-dispersion in liquid form containing a solvent, which may be water or an organic solvent. This dispersion in a liquid allows the carbon nanotubes to be released from their entanglements, but requires large amounts of solvent. Given the small amounts of carbon nanotubes present in these dispersions, large amounts of material need to be transported between the production sites of the carbon nanotubes and their dispersions and the manufacturing sites of the electrodes and batteries using these dispersions, resulting in a very unfavorable carbon footprint.

[0005] Therefore, the amount of solvent required for making these dispersions is minimized, or even a solution to eliminate the solvent is sought. Transporting carbon nanotubes combined with other compounds in a dry form with a high content of carbon nanotubes is an alternative with an optimal carbon footprint. To date, EP2550699 describes a composition comprising carbon nanotubes combined with a solvent and with a polymer that assists in the dispersion of carbon nanotubes. The document describes the manufacture of carbon nanotube / water / carboxymethylcellulose pellets. These pellets can then be dried in an oven and redispersed before preparing the electrode.

[0006] However, during the manufacture of electrodes, these pellets do not achieve electrical properties equivalent to those obtained using dispersions in solvents obtained, for example, by ball milling, which constitutes the method currently used in industry. Therefore, there is no solution to date that allows the formulation of electrodes containing carbon nanotubes under optimal conditions. The dry route of EP2550699 also does not allow optimal electrical performance qualities, or the route in the presence of solvents requires the transportation of large amounts of carbon nanotubes formulated in the presence of solvents.

[0007] Therefore, the applicant sought a dry form, different from pellets, that could be redispersed by the user during the electrode preparation steps. In this way, the volume of material transported is greatly reduced.

[0008] Unexpectedly, the applicant has found that by virtue of certain parameters of density and porosity of the powder, carbon nanotube-polymer compositions can be obtained that are well redispersible and provide performance qualities comparable to the liquid route. These carbon nanotube-polymer compositions in powder form can then be appropriately re-formulated in high-performance electrodes for batteries. In particular, these powders can be combined with the other components of the electrode by returning to the solvent route used to make the electrode, by depositing the mixture in liquid form and then drying the electrode, or by depositing these powders together with the electrode components mixed in solid form and then deposited by a suitable method such as electrostatic spraying, followed by calendering. Summary of the invention

[0009] The present invention relates to a composition comprising carbon nanotubes and at least one polymer in a carbon nanotube / polymer mass ratio of less than 100 / 5, wherein the composition has a loose bulk density of 0.11 to 0.5 g / cm 3 In the form of a powder with a density of 50 to 350 m 2 / g of apparent specific surface area and less than 10% by mass of solvent content. DETAILED DESCRIPTION

[0010] The composition of the present invention has a carbon nanotube / polymer mass ratio of less than 100 / 5, preferably less than 10 / 1, preferably less than 4 / 1, but greater than 1 / 1.

[0011] The composition of the invention is in the form of a powder of spherical particles, the diameter of which varies from a few micrometers to about a hundred micrometers.

[0012] Figure 1 A scanning micrograph of a typical powder of the invention is shown.

[0013] Figure 2 The morphology at the particle surface of a typical powder of the present invention is shown.

[0014] These powders comprising carbon nanotubes can be obtained under certain conditions of drying the dispersion, with atomization (spray drying) being one possibility exemplified by the applicant.

[0015] These dispersions are made from carbon nanotubes, generally of relative density less than 0.1, and at least one polymer, processed under high shear in the presence of a solvent. During the preparation of these dispersions, other compounds may be combined with these dispersions.

[0016] Among the other compounds that can be added to the composition of the invention, mention may be made of carbon fibers, carbon nanofibers, graphene, or also carbon black. Carbon black is preferred. When carbon black is concerned, the mass ratio of carbon nanotubes / carbon black may range from 100 / 1 to 1 / 100, preferably from 100 / 5 to 1 / 5.

[0017] The carbon nanotubes present in the composition according to the invention may be single-walled or multi-walled carbon nanotubes. They are preferably multi-walled. They are present in tangled form or in bundles. They are preferably in tangled form. They may be purified, that is to say freed from residual impurities, in particular metals, present at the end of their synthesis.

[0018] The polymer used in the context of the present invention may be a homopolymer, a random copolymer, a block copolymer, or a gradient copolymer, and these different polymers may be used in combination or alone. Preferably, the polymer has a weight average molecular weight of less than 150 000 g / mol, preferably less than 120 000 g / mol, and more preferably less than 80 000 g / mol, measured by size exclusion chromatography calibrated with polystyrene standards.

[0019] The choice of the polymer or the combination of polymers is adapted to the solvent used for the preparation of the preliminary dispersion comprising carbon nanotubes. The polymer must be soluble in the solvent, that is to say exhibit a homogeneous solution.

[0020] "Soluble" is understood to mean the possibility of dissolving at least 5 g of polymer per liter of solvent and preferably at least 20 g of polymer per liter of solvent at a temperature of 5 to 80°C, preferably 15 to 35°C and more preferably 15 to 25°C.

[0021] Thus, any type of polymer and any type of solvent may be suitable in the context of the present invention, provided that the polymer-solvent pair meets the conditions for solubility.

[0022] The solvent is selected in a non-limiting manner from water, N-methylpyrrolidone, triethyl phosphate, Cyrene TM , dimethyl sulfoxide, dimethylformamide, ketones, acetates, furans, alkyl carbonates, alcohols, and mixtures thereof. The solvent may be CO2 in a supercritical state. The solvent is preferably water.

[0023] The polymer may be a copolymer comprising (meth)acrylic or styrenic monomer entities, at least one of which has a functional group selected from hydroxyl, acid, sulfonic acid, epoxy, amide, ether, ester and pyrrolidone. Among these functional or non-functional monomers, mention may be made of monomers such as methacrylic acid, acrylic acid, dimethylacrylamide, glycidyl methacrylate, hydroxyethyl acrylate, methyl methacrylate, methyl acrylate, and more generally substituted or unsubstituted cyclic or acyclic alkyl (meth)acrylates, as well as substituted or unsubstituted styrene, 2-acrylamido-2-methylpropanesulfonic acid and N-vinylpyrrolidone. The polymer may also be selected from polysaccharides, modified polysaccharides, polyacrylamide homopolymers or copolymers, polyacrylic acid homopolymers or copolymers mainly comprising acrylic acid, polyvinyl alcohol homopolymers or copolymers, polyvinylpyrrolidone homopolymers or copolymers, and mixtures of these polymers.

[0024] Preferably, the polymer used is selected from carboxymethylcellulose, polyvinylpyrrolidone homopolymer or copolymer, polyvinyl alcohol homopolymer or copolymer, polyacrylic acid homopolymer or copolymer mainly containing acrylic acid, and more particularly carboxymethylcellulose (CMC), polyvinylpyrrolidone homopolymer or copolymer, and more preferably polyvinylpyrrolidone homopolymer or copolymer. Regarding polyvinylpyrrolidone homopolymer or copolymer, the weight average molecular weight is 10 000 to 120 000 g / mol, preferably 20 000 to 60 000 g / mol, and more preferably 20 000 to 40 000 g / mol. The polymer with acid functional groups (CMC, polyacrylic acid, etc.) can be alkali metal salts thereof, preferably Li + Or Na + ) form.

[0025] Furthermore, in addition to the polymers already present, halogenated polymers such as PVDF or non-halogenated elastomers are present in combination or otherwise. These are polymers used in the composition of the electrode and they can be added at this stage, ie before the final formulation of the electrode.

[0026] The invention also relates to these compositions in the presence of halogenated polymers such as PVDF or non-halogenated elastomers, alone or in combination.

[0027] The term "PVDF" as used herein includes homopolymers of vinylidene fluoride (VDF) or copolymers of VDF and at least one other comonomer, wherein VDF accounts for at least 50 mol%. Comonomers polymerizable with VDF are selected from vinyl fluoride, trifluoroethylene, chlorotrifluoroethylene (CTFE), 1,2-difluoroethylene, tetrafluoroethylene (TFE), hexafluoropropylene (HFP), perfluoro(alkyl vinyl) ethers, such as perfluoro(methyl vinyl) ether (PMVE), perfluoro(ethyl vinyl) ether (PEVE) or perfluoro(propyl vinyl) ether (PPVE), perfluoro(1,3-dioxazole), perfluoro(2,2-dimethyl-1,3-dioxazole) (PDD), products of the formula CF2=CFOCF2CF(CF3)OCF2CF2X, wherein X is SO2F, CO2H, CH2OH, CH2OCN or CH2OPO3H, products of the formula CF2=CFOCF2CF2SO2F, products of the formula F(CF2) n The product of CH2OCF=CF2, wherein n is 1, 2, 3, 4 or 5, the product of formula R1CH2OCF=CF2, wherein R1 is hydrogen or F(CF2) z , and z has a value of 1, 2, 3 or 4, a product of the formula R3OCF=CH2, wherein R3 is F(CF2) z , and z has a value of 1, 2, 3 or 4, or perfluorobutylethylene (PFBE), fluorinated ethylene propylene (FEP), 3,3,3-trifluoropropene, 2-trifluoromethyl-3,3,3-trifluoro-1-propene, 2,3,3,3-tetrafluoropropene or HFO-1234yf, E-1,3,3,3-tetrafluoropropene or HFO-1234zeE, Z-1,3,3,3-tetrafluoropropene or HFO-1234zeZ, 1,1,2,3-tetrafluoropropene or HFO-1234yc, 1,2,3,3-tetrafluoropropene or HFO-1234ye, 1,1,3,3-tetrafluoropropene or HFO-1234zc, and chlorotetrafluoropropene or HCFO-1224. In the specific case where the process for preparing the composition of the invention in powder form is atomization, the PVDF can be introduced into the composition of the invention in dissolved form or in the form of a latex.

[0028] The non-halogenated elastomer may be of the following type: natural or non-natural rubber, nitrile rubber, NBR (nitrile-butadiene rubber), SBR (styrene-butadiene rubber), substituted polyphosphazenes, acrylic polymers or silicone polymers, optionally in combination of these elastomers.

[0029] According to one variant of the invention, the composition of the invention may also be supplemented with additives and in particular organic carbonates such as ethyl carbonate, propyl carbonate, diethyl carbonate, dimethyl carbonate and fluoroethylene carbonate, alone or as a mixture, and preferably ethyl carbonate, the proportion of organic carbonate relative to the polymer being less than 60% by mass, and optionally hygroscopic agents such as lithium bis(trifluoromethane)sulfonyl imide, lithium hexafluorophosphate, lithium tetrafluoroborate, lithium bis(fluorosulfonyl)imide, lithium perchlorate, lithium hexafluoroarsenate, and 4,5-dicyano-2-(trifluoromethyl)imidazole in the form of the acid or lithium salt, alone or as a mixture, and in particular 4,5-dicyano-2-(trifluoromethyl)imidazole in the form of the acid or lithium salt, a maximum of 50% by mass relative to the carbon nanotubes.

[0030] The invention also relates to these compositions in the presence of these additives.

[0031] The composition of the present invention in powder form can be prepared by various processes, among which there can be mentioned a process of precipitating a composition comprising carbon nanotubes / solvent / polymer with the aid of a non-solvent for the polymer; a process of freeze-drying a composition comprising carbon nanotubes / solvent / polymer, the process comprising a step of extruding the composition comprising carbon nanotubes / polymer, wherein supercritical CO2 is injected during the extrusion step, wherein the mass proportion of supercritical CO2 is 25% to 1000% of the composition, and CO2 is subsequently degassed, or another device using supercritical CO2; or a process of atomizing a composition comprising carbon nanotubes / solvent / polymer.

[0032] During the preparation of the composition of the invention in powder form by one or another of the processes described, additives may be added together to the composition comprising carbon nanotubes and at least one polymer. A powder is then obtained which may comprise carbon nanotubes, at least one polymer and one or more additives.

[0033] According to a preferred embodiment, the composition in powder form is prepared by a process comprising the steps of extruding one of these compositions comprising carbon nanotubes and at least one polymer, wherein supercritical CO2 is injected during the extrusion step, wherein the mass proportion of supercritical CO2 is from 25% to 1000% of the composition comprising carbon nanotubes and at least one polymer, and then degassing the CO2 and recovering the powder.

[0034] Therefore, the present invention also relates to a process for obtaining the composition according to the invention by extruding a composition comprising carbon nanotubes and at least one polymer, wherein supercritical CO2 is injected during the extrusion step, wherein the mass proportion of supercritical CO2 is between 25% and 1000% of the composition, the CO2 is subsequently degassed and the powder is recovered.

[0035] According to a yet more preferred embodiment, the composition in powder form is prepared by an atomization process.

[0036] In the case of atomization, the process is as follows:

[0037] The composition of the present invention is prepared in two steps:

[0038] The first step comprises dispersing the carbon nanotubes in the presence of at least one polymer and a solvent in a suitable device selected from the following: a deflocculator, a ball mill, a z-dispersion device equipped with rotor / stator stirring, ultrasound or a cavitator. These devices are devices that make it possible to dissociate the balls of carbon nanotubes under high shear and to appropriately disperse them in a solvent. A combination of a deflocculator and a ball mill or others is preferred.

[0039] During this step, PVDF and / or non-halogenated elastomers and / or additional compounds such as organic carbonates or moisture absorbers may also be combined.

[0040] The process is carried out with a carbon nanotube-polymer ratio of 3% to 20% by mass and preferably 5% to 10% by mass relative to the solvent. The dispersion thus obtained is then diluted in a solvent so that its viscosity reaches a Brookfield value of 50 to 10,000 centipoise and preferably 100 to 1,500 centipoise. The viscosity values ​​relate to the dispersion and are measured at the end of its preparation. The viscosity of these dispersions may vary slightly over time and exceed 10,000 centipoise.

[0041] For good stability it is recommended to operate at a dispersion pH of 3 to 12 and preferably 5 to 10.

[0042] In the second step, the latter dispersion is atomized by entering a gas stream, which may be air, an inert gas, or a mixture of inert gases, or air and an inert gas, wherein the temperature of the gas entering the atomizer is greater than 120°C, preferably 120°C to 240°C, and more preferably 140°C to 240°C, ideally 200°C to 240°C, and the carbon nanotube / polymer powder is recovered. Drying after atomization may be necessary to reduce the solvent content to less than 0.5% by mass. Alternatively, and depending on the formulation used during the subsequent electrode manufacturing process, a non-halogenated elastomer and / or PVDF in latex form may be added to the composition of the present invention during the atomization stage.

[0043] Therefore, the present invention also relates to a process for obtaining the composition of the present invention by atomization, comprising the steps of:

[0044] - dispersing the carbon nanotubes in a solvent in the presence of at least one polymer,

[0045] - Atomizing the dispersion with a gas heated to a temperature greater than 120° C. and then recovering the powder.

[0046] Preferably, the solvent used during atomization is water.

[0047] The composition of the present invention is in the form of a powder of porous unit particles or an aggregate of porous unit particles, preferably having a particle size corresponding to: D of 4 to 8 μm v 10 value, D from 15 to 30 μm v 50 value, and D between 50 and 100 μm v 90 value, D v Denotes volume mean diameter. The measurement is carried out using a Malvern-type laser diffraction instrument (Mastersizer 3000). Powders with larger or smaller particle sizes will not constitute a departure from the scope of the present invention.

[0048] The powder has a diameter of 50 to 350 m 2 / g and preferably 90 to 200 m 2 The BET measurements were carried out using an ASAP 2460 instrument from Micromeritics.

[0049] The powder has a viscosity of 0.11 to 0.5 g / cm 3 , preferably 0.12 to 0.5 g / cm 3 , and preferably 0.15 to 0.5 g / cm 3 Loose bulk density.

[0050] The powder has a residual solvent content of less than 10%, preferably less than 6%, and more preferably less than 5% by mass.

[0051] The composition of the present invention in powder form can be used for the manufacture of battery electrodes and in particular for the manufacture of cathodes. To manufacture electrodes, the composition of the present invention is mixed with other compounds of the electrode in the form of dispersion in a solvent, or mixed as is with other compounds of the electrode, i.e. mixed in dry form in a suitable mixer.

[0052] During the manufacture of electrode formulations using the composition of the present invention, mixing is preferably performed using an extruder. This is because the applicant has found that an extruder is the device that provides the best conductivity results in formulations for electrodes.

[0053] The invention therefore also relates to electrodes and preferably cathodes made using these powders.

[0054] According to a first preference, the powder of the invention is mixed with lithium NMC (nickel manganese cobalt) oxide, of the LFP (lithium iron phosphate), LMO (lithium manganese oxide) or LMNO (lithium manganese nickel oxide) type, and a fluoropolymer, typically PVDF, and / or a non-halogenated elastomer in a suitable mixer, such as a disk mixer or planetary mixer, and then the solvent is added, if the following are not already present in the composition of the invention. The mixture obtained is deposited on a conducting plate, and the solvent is then evaporated off.

[0055] According to a second preference, which constitutes another advantage of the present invention, the powder of the present invention can be used in a solvent-free electrode preparation process (called "dry process"), that is, the powder of the present invention is directly prepared with powders of other compounds and active materials of the electrode, depending on whether the electrode is an anode or a cathode. Therefore, all the ingredients constituting the electrode can be mixed directly in powder form without a solvent, and the electrode can be formed by: hot lamination / calendering, electrospraying (electrostatic powder deposition), followed by hot lamination.

[0056] Thus, other solvent-free technologies may advantageously use the compositions of the present invention in powder form in the extrusion of active materials for cathodes or anodes formulated directly in liquid or solid electrolytes, thereby producing cathodes or anodes that can be used directly in battery components.

[0057] The invention also relates to the use of the composition of the invention for obtaining electrodes, cathodes or anodes, to electrodes, cathodes or anodes and preferably cathodes obtained using the composition of the invention formulated by the solvent route or in dry form, and also to batteries obtained with these electrodes.

[0058] Example

[0059] The embodiment uses a residual metal content of less than 50 ppm C100 carbon nanotubes (Arkema).

[0060] Example 1: Reference carbon nanotube liquid composition. Comparative, outside the present invention.

[0061] In this example, a typical carbon nanotube composition used in practice so far in industry is reproduced. Thus, the composition comprising carbon nanotubes is a liquid composition with a low content of carbon nanotubes and a high content of solvent. This composition is used in Example 2 for the manufacture of a reference electrode, constituting the goal to be achieved with the composition of the present invention.

[0062] 100g carbon nanotubes, 25g PVP (polyvinyl pyrrolidone) (weight average molecular weight of 24 000g / mol) and 1000g N-methyl pyrrolidone are introduced into a deflocculator. The mixture is homogenized in a deflocculator and then processed in a horizontal ball mill to disperse the particles of the carbon nanotubes. The balls used have a diameter of 0.6mm in diameter, and the duration of grinding is 200-260 minutes. Additional N-methyl pyrrolidone (166g) is added to obtain a fluid and operable (processable) composition.

[0063] The viscosity of the obtained dispersion, denoted Dref, was measured on a Brookfield viscometer. The composition Dref obtained had a carbon nanotube content of 7.68% and a viscosity of 600 centipoise measured at 25°C.

[0064] Example 2: Fabrication of reference electrode (cathode).

[0065] The dispersion Dref obtained in Example 1 is introduced into a planetary mixer, followed by the addition of 95 g of lithium nickel manganese cobalt oxide containing a Ni:Mg:Co ratio of 6:2:2 (known as NMC 622), N-methylpyrrolidone containing PVDF (sold by Arkema under the reference Kynar HSV 1810), for 30 minutes, in order to obtain a slurry with all the constituent compounds of the cathode. The formulation obtained is represented in dry form as follows, in percentages by mass:

[0066] 97.75% NMC 622;

[0067] 1% carbon nanotubes;

[0068] 1% PVDF;

[0069] 0.25% PVP.

[0070] The solids content was 74%.

[0071] The electrodes were prepared by coating using a Sheen film coater and an adjustable BYK-Gardner coater. A 200 μm thick film was applied to a 25 μm thick aluminum foil on a polyethylene terephthalate (PET) sheet constituting an insulating support. Drying was performed in a ventilated oven at 120° C. for 2 hours.

[0072] The dried electrode was then calendared to achieve a final film thickness of approximately 80 μm.

[0073] To calculate the resistivity, the PET-supported electrodes were cut into a 3 x 4 cm format. Silver paint was applied to the ends of the cut bodies. Once the paint had dried, the resistance (R) was measured at 25°C with an ohmmeter.

[0074] The value of the resistance R is a good indicator of the performance of the effect of the carbon based additive, in this case the carbon nanotubes.

[0075] A resistance of 7 ohms was measured on this electrode. This value constitutes a reference and therefore a target to be achieved in the context of the present invention.

[0076] Example 3: Dry form composition of carbon nanotubes according to known prior art. Comparative Example 2, outside the present invention.

[0077] This example was carried out according to EP 2550699.

[0078] 4 kg of carbon nanotubes were mixed with 200 g of PVP (weight-average molecular weight of 24 000 g / mol). After adding 14 L of demineralized water, the mixture was homogenized in a 60 L rotary mixer.

[0079] The mixture is then introduced into the hopper of a Clextral BC21 extruder by a weight metering device set at 15 kg / h, followed by suitable pelletization of the strands obtained. The temperature control system of the extruder is set at 50° C. The speed of the screw is 400 rpm. Cylindrical pellets with a diameter of 4-5 mm and a length of 3-20 mm are obtained.

[0080] The pellets were then dried in a ventilated oven at 140°C for 4 hours.

[0081] The bulk density of the pellets was 1.2 g / cm3. These pellets were ground in a gas jet mill to obtain a v 90<100μm powder. The loose bulk density of the powder after grinding was measured to be 0.85g / cm 3 The obtained powder was recorded as P0 and had a BET measurement of 34 m 2 The BET measurements were carried out using an ASAP 2460 instrument from Micromeritics.

[0082] The loose bulk density (LBD) is defined by the ratio of the mass of a powder to its volume after loosening.

[0083] The measurement was performed as follows: measuring at 100 cm 3 The maximum volume occupied by the powder in a closed graduated cylinder with a mass of T that is slowly turned over several times. Weighing is performed using a balance accurate to 0.1 g.

[0084] The cylinder is filled to three quarters, then weighed to give a mass m1, closed, and then slowly inverted several times until the maximum volume occupied by the powder is obtained. The volume occupied is denoted v in cm 3 count.

[0085] In g / cm 3 The loose bulk density is calculated by the following formula:

[0086] LBD=(m1-T) / v

[0087] Example 4: Composition of carbon nanotubes and PVP according to the present invention

[0088] The composition described in Example 1 was prepared in the same manner, but using water instead of N-methylpyrrolidone.

[0089] The solid composition was as follows: 100 g of carbon nanotubes and 25 g of poly(vinyl pyrrolidone) (PVP), wherein the carbon nanotube / PVP mass ratio was 4 / 1. The mixture was homogenized with 1000 g of water in a deflocculator and then ground in a horizontal ball mill as described in Example 1. Additional amounts of water were added during grinding to adjust the viscosity.

[0090] At the end of grinding, the solid content was 6% by mass, and the proportion of carbon nanotubes was 4.8%. The final viscosity was 500 centipoise.

[0091] The aqueous dispersion is then dried in an atomizer. The dispersion is sprayed in the presence of an air stream preheated to different temperatures.

[0092] Under the conditions given in Table 1, solid compositions P1 to P4 were collected in powder form at the outlet of the atomizer.

[0093] [Table 1]

[0094] Table 1 T LBD H S G P1 120 0.38 6 34 P2 160 0.32 3.84 92 6 / 19 / 63 P3 200 0.31 4.95 117 7 / 24 / 88 P4 240 0.28 1.95 158 6 / 19 / 65

[0095] T: Temperature of preheated air entering the atomizer ℃.

[0096] LBD: loose bulk density.

[0097] H: mass % of residual water.

[0098] S: apparent specific surface area, BET m 2 / g.

[0099] G: Particle size distribution, in μm v 10 / D v 50 / D v 90.

[0100] The four powder samples P1 to P4 obtained at the end of the atomization were then treated in a vacuum oven to remove residual moisture.

[0101] The formulation of this example in powder form was used directly in the formulation of an NMC cathode type electrode, as described in Example 2.

[0102] All formulations obtained in this example have a much lower bulk density than the solid ground aggregates (P0) of Example 3. P2, P3 and P4 have a larger apparent specific surface area than P0 and P1.

[0103] Example 5: Production of cathode ink and evaluation of cathodes with carbon nanotube powders P1 to P4 and sample P0 of Example 3

[0104] Two methods were used to prepare cathodes of the formulation described in Example 2.

[0105] Method 1: Formulation is the same as in Example 2, but powders P0 to P4 are used instead of dispersion Dref of Example 1.

[0106] NMC 622, PVDF Kynar HSV8010 and powders P0 to P4 were dry premixed in a planetary mixer and then in a disk mixer at 50° C. for 40 minutes. N-Methylpyrrolidone was gradually added to keep the viscosity of the cathode ink obtained within a value of 6000-10 000 centipoise.

[0107] Method 2: Using this method, cathode slurry is made from the ground pellet dry products P0, P1 to P4 powders obtained by atomization and active materials and PVDF binder according to the original extrusion method. In this case, liquid Dref cannot be used. A micro extruder sold by DSM is used to continuously extrude a mixture of NMC 622 and PVDF Kynar HSV8010 with powders P0 to P4. NMP and then powder P are introduced together with a mixture of NMC 622 and PVDF Kynar HSV8010. NMP is added to the solid mixture and adjusted to obtain a viscosity of 6000 to 10 000 centipoise of the resulting ink, and is used to produce an electrode as described in Example 2.

[0108] Follow the same steps for powders P0 to P4:

[0109] - 9.35 mL of NMP was introduced into the extruder and preheated to 50 °C;

[0110] Once the NMP had been introduced, the screw speed was increased to 240 rpm;

[0111] - 42.6 g of powder P were gradually introduced within 30-60 seconds together with the mixture of NMC 622 and PVDF Kynar HSV8010; the torque was continuously monitored; the torque was adjusted with NMP to remain in the range of 1000-1400 N.m.

[0112] - Once the torque has stabilized, 4.9 g NMP is gradually introduced over 30-60 seconds; the torque is gradually reduced to 100 N.m.

[0113] - The cathode ink is collected at the extruder outlet. The solids content is 76-78%. The 5 cathode inks obtained with the 5 powders P0, P1, P2, P3 and P4 are used to produce the electrodes as described in Example 2.

[0114] The cathodes produced from inks obtained by the two methods as described in Example 2 have similar thicknesses of the order of 78-82 μm and their resistances are given in Table 2. It can be seen the values ​​of the reference cathode produced from a liquid dispersion according to a conventional method.

[0115] [Table 2]

[0116]

[0117]

[0118] These results show that the cathode obtained from the composition of the invention shows better electrical properties than those of the prior art, such as the powder (P0) obtained from the granules of EP2550699, but gives the same results in terms of electrical properties as the NMP-based carbon nanotube dispersion of Example 1 (Dref). The particles of lower relative density produced by atomization at a gas flow temperature greater than 120° C. show results close to the reference. It can therefore be concluded that the carbon nanotubes that can be used in such applications must have a relative density of less than 0.5.

[0119] The extrusion method (method 2) gave results closest to the reference of example 2. The use of powder P0 obtained from granules of EP 2550699 gave results which always remained variable with respect to the product of the invention.

[0120] Example 6: Measurement of absorbance.

[0121] The dry powders (P0 and P4) were introduced at 6% by mass into NMP at ambient temperature.

[0122] After mixing for 30 min with a pan mixer at 600 rpm, the exact solids content was assessed with a thermobalance. Solutions diluted to 50 +- 2 ppm were prepared.

[0123] The absorbance was measured using a HACH DR1900 spectrophotometer at a light wavelength of 360 nm.

[0124] Absorbance (A), also known as optical density (OD), is the amount of light absorbed by a dispersion. The greater the absorbance A, the better the distribution of the particles in the volume of the dispersion (Table 3).

[0125] [Table 3]

[0126] Table 3 Absorbance A Example 1 Dispersion of Dref 3.2-3.4 Dispersion with P0 2.2-2.6 Dispersion with P4 3-3.4

[0127] The dispersion produced from the powder P4 of the invention has an absorbance comparable to that of the dispersion Dref of Example 1 and much higher than that obtained from P0, demonstrating the good distribution of the carbon nanotubes obtained from P4 in the solvent.

[0128] Embodiment 7:

[0129] This example evaluates the synergistic effects of the combination of carbon black and carbon nanotubes in electrodes made using the composition of the invention compared to those of the prior art compositions (solvent type route of Example 1, route using pellets P0 obtained from EP 2550699 and drying by mixing P2 with carbon black).

[0130] The combination with carbon black during the atomization step gave the best results. (Table 5)

[0131] The electrode is prepared according to the formula with the component ratio in Table 4:

[0132] [Table 4]

[0133]

[0134] Table 5 shows the resistance measured on cathodes produced by the four ways of mixing carbon nanotubes and carbon black. Once formulated into an electrode, mixing prior to atomization of the composition according to the invention has the best properties. Using the procedure and composition of the invention, the carbon nanotube / carbon black synergy is greatest.

[0135] [Table 5]

[0136]

Claims

1. A composition comprising carbon nanotubes and at least one polymer in a carbon nanotube / polymer mass ratio of less than 100 / 5, wherein the composition has a loose bulk density of 0.11 to 0.5 g / cm 3 in the form of a powder having a particle size of 50 to 350 m / s as measured by a Micromeritics ASAP 2460 instrument. 2 / g apparent specific surface area and less than 10% by mass content of solvent, wherein the polymer is selected from modified polysaccharides, polyvinyl pyrrolidone homopolymers or copolymers, and the loose bulk density (LBD) is defined by the ratio of the mass of the powder to its volume after loosening, and the measurement is carried out as follows: measuring at 100cm 3 The maximum volume occupied by the powder in a closed graduated cylinder of mass T which is slowly turned over several times, wherein the weighing is performed using a balance accurate to 0.1 g and the cylinder is filled to three quarters, then weighed to obtain a mass m1, closed, and then slowly turned over several times until the maximum volume occupied by the powder is obtained, denoted v, in cm 3 Calculated in g / cm 3 The loose bulk density is represented by and calculated by the following formula: LBD=(m1-T) / v.

2. A composition as claimed in claim 1, wherein the polymer is selected from polyvinylpyrrolidone homopolymers or copolymers having a molecular weight of 20 000 to 60 000 g / mol.

3. The composition as claimed in claims 1 to 2, further comprising carbon black in a carbon nanotube / carbon black mass ratio ranging from 100 / 1 to 1 / 100.

4. The composition according to any one of claims 1 to 3, further comprising at least one organic carbonate, such as ethyl carbonate, propyl carbonate, diethyl carbonate, dimethyl carbonate and fluoroethylene carbonate, alone or as a mixture.

5. The composition of any one of claims 1 to 4, further comprising at least one compound selected from the group consisting of lithium bis(trifluoromethane)sulfonyl imide, lithium hexafluorophosphate, lithium tetrafluoroborate, lithium bis(fluorosulfonyl)imide, lithium perchlorate, lithium hexafluoroarsenate, and 4,5-dicyano-2-(trifluoromethyl)imidazole in the form of an acid or lithium salt, alone or as a mixture, and in particular 4,5-dicyano-2-(trifluoromethyl)imidazole in the form of an acid or lithium salt.

6. The composition as claimed in claims 1 to 5, further comprising PVDF, homopolymer or copolymer, and / or a non-halogenated elastomer.

7. A process for preparing a composition as claimed in any one of claims 1 to 6, using an atomizer and comprising the following steps: - preparing a composition as claimed in any one of claims 1 to 6 in a deflocculator at a temperature of 5° C. to 80° C. in the presence of a solvent to obtain a dispersion comprising carbon nanotubes, - Atomizing the dispersion with a gas heated to a temperature greater than 120° C. and recovering the powder.

8. A process for preparing a composition as claimed in any one of claims 1 to 6, comprising the steps of extruding the composition, wherein supercritical CO2 is injected during the extrusion step, wherein the mass proportion of supercritical CO2 is 25% to 1000% of the composition, followed by degassing the CO2 and recovering the powder.

9. Use of the composition according to any one of claims 1 to 6 for the manufacture of an electrode with or without a solvent.

10. Electrode obtained by the use according to claim 9.

11. A battery comprising at least one electrode as claimed in claim 10.

Citation Information

Patent Citations

  • Masterbatch of carbon-based conductive fillers for liquid formulations, especially in Li-ion batteries

    CN108003359A

  • Composite conductive powder and preparation method thereof

    CN113436779A

  • Pulverulent composition based on carbon nanotubes, methods of obtaining them and its uses, especially in polymeric materials

    US20090176924A1

  • Method for producing powdery polymer / carbon nanotube mixtures

    US20140001416A1